Change in gray matter volume and cerebral blood flow in patients with burning mouth syndrome - Lee, Young Chan; Jahng, Geon‐Ho; Ryu, Chang‐Woo; Byun, Jae Yong (Journal of oral pathology & medicine, 2019)
Background The purpose of this study was to evaluate alterations in gray matter volume (GMV) and cerebral blood flow (CBF) using structural MRI and arterial spin labeling (ASL) perfusion MRI, respectively, in burning mouth syndrome (BMS) patients Methods We prospectively enrolled 12 patients with BMS and 14 healthy controls. Volumetric T1‐weighted magnetization‐prepared rapid gradient‐echo imaging and pseudo‐continuous ASL were performed to obtain GMV and CBF, respectively. We analyzed differences in the GMV and CBF between the two groups, and their correlations with clinical parameters. Results The GMV was smaller in the left thalamus and left middle temporal gyrus in the BMS group when compared to controls. Regional CBF in the BMS group was significantly decreased in the left middle temporal gyrus, left insula, right middle temporal gyrus, and right insula compared with controls. In BMS patients, there was a significant correlation between GMV and pain severity in the left middle temporal gyrus. Conclusion The reduced GMV seen in the thalami of BMS patients is consistent with the pattern observed in those with chronic pain disease, which implies that the pathogenesis of BMS may be associated with atrophy of the brain structures associated with thalamocortical processing. In addition, changes in CBF in the insula and middle temporal gyrus were also observed.